Analisis Pengaruh Operating Expenses to Operating Income (Rasio Bopo), Cost Efficiency Ratio dan Non Performing Loan Terhadap Net Profit Margin Pada Perbankan di Bursa Efek Indonesia Periode Tahun 2015-2019 - Sulasmy, Widiya; Cahyaningtyas, Niken Wahyu (Konsentrasi: Jurnal Manajemen dan Bisnis, 2021)
The aims of this research are: 1). Analyzing the effect of operating expenses to operating income (BOPO ratio) on the net profit margin, 2). Analyzing the effect of the cost efficiency ratio on the net profit margin, 3). Analyzing the effect of non-performing loans on the net profit margin, 4). Analyzing the effect of operating expenses to operating income (BOPO ratio), cost efficiency ratio and non-performing loans simultaneously on the net profit margin. The research method used in this research is descriptive and associative or relationship research. While the data analysis method used is descriptive statistics and inferential statistics. Based on the results of this study prove that 1). The results of the calculation of simple regression analysis obtained the probability value of the sig value of 0.000. Because the sig value of 0.000 <0.05, it can be interpreted that there is a significant effect of operating expenses to operating income (BOPO ratio) on the net profit margin. 2). The results of the calculation of simple regression analysis obtained the probability value of the sig value of 0.023. Because the value of sig 0.023 <0.05, it can be interpreted that there is a significant effect of the cost efficiency ratio on the net profit margin. 3). the results of the calculation of simple regression analysis obtained the probability value of the sig value of 0.023. Because the value of sig 0.000 <0.05, it can be interpreted that there is a significant influence of non-performing loans on the net profit margin, 4). the results of the calculation of multiple regression analysis obtained the probability value of the sig value of 0.000. Because the sig value of 0.000 <0.05, it can be interpreted that there is a significant effect of operating expenses to operating income (BOPO ratio), cost efficiency ratio and non-performing loan simultaneously on the net profit margin.